Tourism Marketing Strategy In Ambon City - Albertus Lalaun; Victor Cornelis; Theofilus J.F.K. Matrutty (Pusat Riset dan Inovasi Nasional, 2023)
The increasing number of tourist destinations and investment makes the tourism sector a key factor in increasing foreign exchange, job creation, business development, and infrastructure. Indonesia, known as a country with a wide range of potential, is able to attract many people to come and explore its uniqueness. Not surprisingly, tourism has been made a priority development program that has always been targeted at achievement by the government. In the last five years, the number of tourist visits to Indonesia has continued to increase. This number of visits has definitely influenced the growth of foreign exchange in Indonesia. In 2021, Indonesian tourism will rank second as the country's foreign exchange contributor after the palm coconut sector, with a value of 20.9 billion. However, even though currency and tourist visits have increased, it turns out that not all Indonesians enjoy the